2017
DOI: 10.1298/ptr.e9898
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation improves prognosis and activities of daily living in hemodialysis patients with low activities of daily living

Abstract: ABSTRACT. Background: Activities of daily living (ADL) in aged hemodialysis patients decrease by many factors as hemodialysis therapy, various disease-related complications and underlying disease for rehabilitation. But the correlation between low ADL and mortality remains unclear. We assessed the levels of ADL and effects of rehabilitation in hemodialysis patients with low ADL. Moreover, the association between the baseline functional independence measure (FIM) or rehabilitation treatment effects and all-caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…Consistent with this expectation, recent studies show the magnitude of improvement with rehabilitation, in patients recently started onto dialysis, to be similar to that of non-dialysis patients [ 6 8 ]. The study population has similar characteristics to other studies of dialysis patients suggesting low risk of selection bias and that our findings may be widely generalizable [ 9 – 21 ]. For example, Forrest et al, reported that the median change in FIM scores, in 40 HD patients, with a mean age of 69 years, undergoing inpatient rehabilitation was similar to our population (a change from mean baseline scores of 80 to 104 by discharge) [ 11 ].…”
Section: Discussionsupporting
confidence: 65%
“…Consistent with this expectation, recent studies show the magnitude of improvement with rehabilitation, in patients recently started onto dialysis, to be similar to that of non-dialysis patients [ 6 8 ]. The study population has similar characteristics to other studies of dialysis patients suggesting low risk of selection bias and that our findings may be widely generalizable [ 9 – 21 ]. For example, Forrest et al, reported that the median change in FIM scores, in 40 HD patients, with a mean age of 69 years, undergoing inpatient rehabilitation was similar to our population (a change from mean baseline scores of 80 to 104 by discharge) [ 11 ].…”
Section: Discussionsupporting
confidence: 65%
“…The identification of a correlation between ADL disability and PDF prevalence/severity opens a scenario of interventions that may ultimately improve PDF. In fact, functional impairment may be prevented, reversed or delayed in patients on chronic hemodialysis through an adequate rehabilitation . Various approaches have been proposed in hemodialysis patients such as environmental adaptations, psychosocial, physical and cognitive interventions, training and education and adaptive aids .…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 , 23 ] Although a prospective study reported that ADL is influenced by age, [ 22 ] the Barthel index was not correlated with age in our cohort (Spearman's rho = 0.574). This may indicate that improvement of ADL through rehabilitation may decrease mortality in this population as ADL, [ 23 ] unlike age, is a modifiable factor.…”
Section: Discussionmentioning
confidence: 71%